The impact of sphygmomanometer placement and cuff placement on blood pressure measurements - Zhu, Xiao-Yong; Zhang, Pu-Hua; Huang, Wen-Yin; Huang, Wan; Tang, Xin-Hu; Yu, Hua; Wang, Su-Nan (Frontiers in Cardiovascular Medicine, 2024)
Background: Hypertension is the most significant global risk factor for mortality and morbidity, making standardized blood pressure measurement crucial. Objectives: Investigate whether the location of blood pressure monitors and the positioning of cuffs yield differing results in blood pressure measurements. Methods: Patients admitted to the Affiliated Hospital of Jiujiang College from January 1, 2022, through June 30, 2023, were enrolled in this study and randomly allocated into four groups. These groups were defined based on the positioning of monitoring equipment as follows: varied placements of cuffs on automatic blood pressure monitors, different heights for mercury column blood pressure monitors, varied heights for automatic blood pressure monitors, and different orientations for the cuff airbag tubes on electrocardiogram monitors. Blood pressure was measured and recorded for each group, followed by an analysis of the variations in readings across the different setups. Results: In the first cohort of 763 individuals, mean systolic blood pressure measured at the standard upper arm site was 128.8±10.5 mmHg, compared to 125.3±10.4 mmHg at the elbow fossa. Corresponding diastolic pressures were 79.2±10.7 mmHg and 75.0±10.6 mmHg, respectively. The difference in systolic pressure between these positions was significant at 3.48±3.22 mmHg (t₁=29.91, P₁<0.001) and for diastolic pressure at 4.23±1.31 mmHg (t₂=88.98, P₂<0.001). For the subsequent groups, involving 253, 312, and 225 subjects respectively, blood pressure measurements were analyzed and compared across different methods within each group. All P-values exceeded 0.05, indicating no statistically significant differences. Conclusions: Blood pressure values measured at the elbow fossa position using an upper arm-type automatic sphygmomanometer were found to be lower than those measured at the upper arm position, with a difference of 3.48 mmHg for systolic and 4.23 mmHg for diastolic pressures. It is therefore essential to position the cuff correctly, specifically 2-3 centimeters above the elbow fossa, when utilizing an upper arm-type automatic sphygmomanometer for blood pressure monitoring. Conversely, the placement of the mercury column sphygmomanometer and the automated sphygmomanometer at varying heights had no significant effect on blood pressure readings. Similarly, the orientation of the electrocardiogram's cuffed balloon tube, whether facing upward or downward, did not influence blood pressure measurement outcomes.